2018
DOI: 10.4269/ajtmh.17-0411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Health-Care Charges in Murine Typhus: Need for Improved Clinical Recognition and Diagnostics for Acute Disease

Abstract: Murine typhus, caused by , is an undifferentiated febrile illness with no available rapid and sensitive diagnostic assay for use during early disease. We aimed to compare the health-care charges in those diagnosed with murine typhus to those with influenza, a febrile illness with an available rapid diagnostic test. A comparison of health-care-associated charges at the University of Texas Medical Branch at Galveston demonstrated a median of $817 for influenza versus $16,760 for murine typhus ( < 0.0001). Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Because the symptoms of murine typhus can be nonspecific, it can be challenging to diagnose in a timely manner. 4 8 This is especially true during the current COVID-19 pandemic where the non-specific presenting symptoms of murine typhus—fever, headache and myalgia—overlap with symptoms of COVID-19. The symptom overlap of fever, reported in over 90% of patients with murine typhus and in 83%–98% of patients with COVID-19, may blind the clinician from exploring the broader differential diagnoses of other febrile illness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the symptoms of murine typhus can be nonspecific, it can be challenging to diagnose in a timely manner. 4 8 This is especially true during the current COVID-19 pandemic where the non-specific presenting symptoms of murine typhus—fever, headache and myalgia—overlap with symptoms of COVID-19. The symptom overlap of fever, reported in over 90% of patients with murine typhus and in 83%–98% of patients with COVID-19, may blind the clinician from exploring the broader differential diagnoses of other febrile illness.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Early recognition of this disease and prompt intervention with doxycycline will result in more favourable outcomes. 4 During this pandemic, medical providers should develop more comprehensive differential diagnoses in patients who experience persistent symptoms that overlap with COVID-19 and repeatedly test negative for it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review showed a mean duration of fever of up to 15 days and a high rate of hospitalisation and complications in untreated patients. Since treatment with doxycycline has been shown to lead to a cessation of fever with a mean of 3 days [4,5] and a recent study [6] found significantly higher healthcare charges for murine typhus patients when compared with influenza, the importance of early diagnosis and treatment of this neglected disease cannot be overstated. That it is readily treatable with tetracyclines [5] should encourage more clinical awareness as an inexpensively and simply treatable infectious disease that can lead to complications.…”
Section: Resultsmentioning
confidence: 99%